Characteristics of pediatric e-referrals through SMARC system: a two-year national analysis - Alharbi, Abdullah A.; Muaddi, Mohammed A.; Binhotan, Meshary S.; Alqassim, Ahmad Y.; Alsultan, Ali K.; Arafat, Mohammed S.; Aldhabib, Abdulrahman; Alaska, Yasser A.; Alwahbi, Eid B.; Moafa, Hussain A.; Gohal, Gassem; Alabdulaali, Mohammed K.; et al. (Frontiers in Medicine, 2025)
BackgroundElectronic referral (e-referral) systems are increasingly vital for coordinating pediatric healthcare services, yet comprehensive analyses of nationwide implementation remain limited. This study examines patterns, outcomes, and system performance of pediatric e-referrals across Saudi Arabia’s healthcare network.MethodsWe conducted a retrospective analysis of all pediatric e-referrals (n = 62,206) processed through the Saudi Medical Appointment and Referral Center between January 2023 and December 2024. Data analysis included referral types, subspecialty distribution, regional patterns, acceptance rates, and temporal trends.ResultsMale patients represented 54.19% of e-referrals. We found a predominance of routine outpatient referrals (56.98%), with urgent and lifesaving cases comprising 32.41%. The overall acceptance rate was 91.52%, with 100% acceptance for lifesaving cases. Internal referrals constituted 82.85% of cases. General Pediatric Care (31.61%) accounted for most e-referral followed by Pediatric Cardiology (12.12%), Neurological Diseases (11.79%) and Neonatal Care (11.21%). Temporal analysis revealed an increase in overall referrals from 2023 (48.74%) to 2024 (51.26%).ConclusionThis first comprehensive analysis of Saudi Arabia’s pediatric e-referral system demonstrates successful implementation of a coordinated care network with high acceptance rates and effective regional self-sufficiency. The findings provide valuable insights into healthcare planning and resource allocation. These findings offer transferable insights for international healthcare systems implementing pediatric e-referral platforms and digital health initiatives.